2001
DOI: 10.1006/mthe.2001.0300
|View full text |Cite
|
Sign up to set email alerts
|

Transgene Expression in Mouse Airway Epithelium by Aerosol Gene Therapy with PEI–DNA Complexes

Abstract: Gene therapy targeted at the respiratory epithelium holds therapeutic potential for diseases such as cystic fibrosis and alpha-1 anti-trypsin deficiency. A variety of approaches such as intranasal or intratracheal instillation and aerosol delivery have been utilized to target genes to the airways. Polyethylenimine (PEI), a linear or branched polycationic polymer, has been used for delivery of genes to various organs. In this study, using fluorescein isothiocyanate (FITC)-labeled branched PEI, we initially exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 26 publications
2
77
0
3
Order By: Relevance
“…One possibility is because of the long -term expression of CAT (about a month ), which could have some growth inhibitory effect. 18 In addition to the results achieved here with p53 and the nude mouse osteosarcoma lung metastases model, we have also shown previously that aerosolized PEI formulations of p53 results in a significant antitumor response and extended survival in a murine melanoma ( B16 -F10 melanoma in C57 BL / 6 mice) model. 7 These two models differ considerably.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…One possibility is because of the long -term expression of CAT (about a month ), which could have some growth inhibitory effect. 18 In addition to the results achieved here with p53 and the nude mouse osteosarcoma lung metastases model, we have also shown previously that aerosolized PEI formulations of p53 results in a significant antitumor response and extended survival in a murine melanoma ( B16 -F10 melanoma in C57 BL / 6 mice) model. 7 These two models differ considerably.…”
Section: Discussionsupporting
confidence: 78%
“…A detailed description of the deposition of aerosolized PEI and transgene expression in the lungs is described elsewhere. 18 Anticancer studies reported here showed that aerosol delivery of p53wt and the synthetic p53 variant CD -1 caused a significant reduction in lung metastases in a nude mouse model of osteosarcoma. The lung weights and tumor burden for the p53-treated groups were significantly reduced when compared to untreated mice as well as to mice treated with PEI alone or with PEI -pCMVCAT.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…[36][37][38] The most successful cases occur after intranasal or intratracheal administration, when targeting airway epithelial cells. 3,5,9,39 Tissues containing nondividing cells (as in muscle) or slow mitotic cells (as in the liver) are very attractive targets because pDNA can remain for a long time inside the cells. 40 In relation to the relatively fast kinetics seen here, we do not exclude the possibility that the decrease in expression after 5-7 days may be indicative of toxicity.…”
Section: Discussionmentioning
confidence: 99%